The Effect of Logarithmic Total Assets and Liabilities on Log Net Income in Trading Companies Listed on the Indonesia Stock Exchange - Ayuvera Ray; Suhartati (Journal of Sustainable Economics, 2026)
company's financial position is crucial to analyze, particularly for stakeholders. A company’s financial condition and structure can be reflected through two key components in its financial statements: total assets and total liabilities. This study examines how these two variables affect net income, by transforming all data into natural logarithmic form. The data was obtained from eight trading companies listed on the Indonesia Stock Exchange (IDX), for the period 2021-2024. Multiple linear regression was used to assess the influence of log total assets and log total liabilities on log net income. The results suggest that, within the observed sample, both variables significantly affect log net income. However, when examined individually, only log total liabilities have a significant effect on log net income, while log total assets show no significant effect. These findings indicate that a firm's financing structure through liabilities plays an important role in influencing net income, more so than the size of its assets.